Message in a bottle: Analyses of 12–13th century vessels from an Ishmaelite settlement in Orosháza, Hungary. (August 2021) - May, Zoltán; Rózsa, Zoltán; Kreiter, Attila
Highlights: Two ceramic assemblage of settlements from the 12-13th centuries were analysed. Microscopic fabric and geochemical analyses (ICP-OES and ICP-MS) were applied. So called 'white clay' have different provenance (imports) from the other bottles. Multivariate data analysis was applied for evaluating chemical data of samples. Results obtained indicate that many of the analysed bottles are probably imports. Abstract: In the southern part of the Great Hungarian Plain, at Orosháza, excavations were carried out on both sides of a former river between 2004 and 2006. In this study we focus on the ceramic material of the Árpádian Age settlement, in particular ceramic bottles, which are common here but at other Árpádian Age settlements appear rarely. The stylistic features of bottles and their analogies indicate that the community that lived here had a complex social network not only within the Hungarian Kingdom but also in the Balkans in the 12th and 13th centuries. The site itself is also unique: pig bones are completely absent in the animal bone assemblage, meanwhile in other Árpádian Age settlements pig bones are common. Moreover, burials have special rites, and graves have a sidewall niche where the dead were placed oriented to the south. These features, together with a known place name of the area called 'Böszörményestelek' ( parcel of Ishmaelites), indicate that a Muslim community lived here in the 12-13th centuries. The aim of this study is to analyse ceramic bottles and compare their raw materials with other vessel types. To assess the provenance of the bottles, we also compare their raw materials with Avar vessels. In order to better understand ceramic production and provenance, microscopic fabric- and geochemical analyses (ICP-OES, ICP-MS) were applied. Bottles, just as other vessel types, were made from several raw materials. The results suggest that the raw materials of bottles made from a so called 'white clay' have different provenance from the other bottles, they are imports, while the raw materials of other bottles also show variability indicating different provenance. At the same time, the raw materials of some of the bottles even correlate with other, assumedly locally made vessels and even with Avar vessels. The utilization of multiple interdisciplinary methods highlights the complex relationships and social networks of this Muslim community in a large area.